ISOLATION AND GROWTH OF DINOFLAGELLATE, Scrippsiella sp. AND DIATOM, Melosira cf. moniliformis IN CONTROLLED CONDITIONS - Wa Iba (Indonesian Aquaculture Journal, 2014)
The growth of the dinoflagellate, Scrippsiella sp. from Narragansett Bay, USA and the chain-forming benthic diatom, Melosira cf. moniliformis from Kendari Bay, Indonesia was evaluated under optimized laboratory conditions to investigate potential new candidates for shrimp aquaculture hatchery feeds. Isolation of microalgae was performed using capillary pipets in f/8-Si for Scrippsiella sp. and f/2 for M. cf. moniliformis. Isolated cells were placed in an incubator with a photoperiod of 12:12 hour (light : dark cycle), at light intensities of 62-89 μmol photons.m-2.s and at temperature of 20oC. Microalgae cells were cultured in 150-mL Erlenmeyer flasks containing 100 mL of f/2-Si medium for Scrippsiella spin triplicates and in 50-mL culture tubes containing 20 mL of f/2 medium for M. cf. moniliformis in four replicates. The cells in culture flasks were used in cell counting experiments while those in tubes were for fluorometer trials. Growth evaluation was conducted every 2-3 days. The diatom, M. cf. moniliformis was in logarithmic phase when observed at 2 to 7 days after inoculation and showed a high growth rate (μ = 0.52 day-1) and high division rate (k = 0.76 day-1, 1 division every 1.3 days). Logarithmic phase of Scrippsiella in culture flasks was started on day 7 to 30 (μ = 0.17 day-1 and k = 0.25 day-1 or 1 division every 4 days). In culture tubes, Scrippsiella sp. reached logarithmic phase at day 21 to 47 (μ = 0.12 day-1 and k = 0.18 day-1, 1 division every 5.65 days). This study indicates that M. cf. moniliformis can be used for aquaculture hatcheries feed but further study for the nutrition composition is needed. Scrippsiella sp. is potentially toxic for aquaculture at high densities, therefore they should be assessed carefully if used for aquaculture feeds.